2010
DOI: 10.1111/j.1440-1827.2010.02560.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphohistiocytoid mesothelioma of the pleura

Abstract: Lymphohistiocytoid mesothelioma (LHM), reported to be a rare variant of sarcomatoid mesothelioma, is challenging to differentiate from non-Hodgkin's lymphoma due to marked lymphocytic infiltration. To aid accurate recognition of LHM, we examined immunohistochemical, in situ hybridization (ISH) of Epstein-Barr virus RNA (EBER-1) mRNA, fluorescence ISH (FISH) for homozygous deletion of 9p21, and asbestos analysis in four cases (three men and 1 woman). Three patients died, while Case 4 was still alive 19 months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…All antibodies were incubated overnight at 4°C. The monoclonal and polyclonal antibodies used are listed in table 2, together with the antigen-retrieval conditions 21 22…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All antibodies were incubated overnight at 4°C. The monoclonal and polyclonal antibodies used are listed in table 2, together with the antigen-retrieval conditions 21 22…”
Section: Methodsmentioning
confidence: 99%
“…Tissue sections on slides were deparaffinised and hydrated to distilled water, and examination was performed in the same way as in our previous study 21. Only individual and well delineated cells were scored.…”
Section: Methodsmentioning
confidence: 99%
“…Sarcomatoid MMs usually consist of spindle cells but can be composed of lymphohistiocytoid cells and/or may also contain heterologous rhabdomyosarcomatous, osteosarcomatous, or chondrosarcomatous elements. 24,25 Mixed or biphasic MMs contain both epithelioid and sarcomatoid areas within the same tumor. [26][27][28][29][30][31][32] In general, the differential diagnosis for MM depends on its basic histologic category: the differential diagnosis for epithelioid MM includes carcinomas and epithelioid cancers; the differential diagnosis for sarcomatoid MM includes sarcomas and other spindle cell neoplasms; and the differential diagnosis of mixed MM includes mixed or biphasic tumors such as synovial sarcoma and metastatic pleomorphic carcinoma of lung.…”
Section: Histologic Features Of MMmentioning
confidence: 99%
“…Galateau-Sallé et al 3 suggested that the survival  in  patients with LHM is more like that of the epithelioid or biphasic subtype of MPM. On the other hand, Kawai et al 4 reported a patient diagnosed with LHM whose autopsy indicated sarcomatous mesothelioma.…”
Section: Discussionmentioning
confidence: 99%